Entrepreneurship Unleashed: Understanding Entrepreneurial Education outside of the Business School. (4th October 2017) - Turner, Tobin; Gianiodis, Peter
Abstract : A growing trend in entrepreneurship education is the development of blended entrepreneurial programs (BEPs)—programs that merge entrepreneurial curriculum with a technical degree—located outside traditional business school settings. In this paper we suggest that individual, student‐level attributes may be as important to entrepreneurial outcomes as curricular considerations in BEPs. Using data from current and recent graduates of a BEP our study suggests that personal attributes—an individual's entrepreneurial passion—increase the likelihood of entrepreneurial intention among its students. Consequently, our findings indicate that BEPs may need to consider applicant characteristics to maximize the likelihood of entrepreneurial outcomes from its program.